Hyperemesis Gravidarum with Gestational Transient Thyrotoxicosis Inducing Thyrotoxic Periodic Paralysis in Diabetes Mellitus and Hypertension: A Case Report - Yovita Gotama; Dewi Catur Wulandari (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Hyperemesis gravidarum (HG) is often associated with gestational transient thyrotoxicosis (GTT) due to elevated human chorionic gonadotropin (hCG) levels, affecting approximately 60% of HG patients. GTT is generally self-limiting, resolving by the first or early second trimester without requiring pharmacological treatment. We present the case of a 38-year-old pregnant woman, in her third pregnancy, who experienced severe nausea and vomiting at 6 weeks of gestation, with a Pregnancy-Unique Quantification of Emesis/Nausea (PUQE) score of 12. Laboratory findings indicated low thyroid-stimulating hormone (TSH) and high free thyroxine (FT4), consistent with GTT, while thyroid ultrasound showed no abnormalities. The patient had a history of chronic hypertension since her first pregnancy and diabetes mellitus diagnosed a year earlier. Three weeks later, she was readmitted and diagnosed with thyrotoxic periodic paralysis (TPP) secondary to GTT. Treatment included intravenous fluids, potassium supplementation, antiemetics, vitamins, antithyroid drugs, and continued management of her diabetes and hypertension. HG, which is most common in the first trimester, is often linked to thyroid dysfunction due to hCG stimulation. While GTT is typically self-limiting, complications like TPP can arise, adding complexity to patient management, especially with coexisting conditions like diabetes and hypertension. Treatment strategies focused on symptom control, fluid rehydration, and careful adjustments of medications for thyroid, glycemic, and blood pressure management. Unfortunately, the patient did not return for follow-up, limiting further evaluation of her thyroid function in the second trimester. This case highlights the need for accurate diagnosis and timely intervention to prevent severe maternal and fetal outcomes, particularly in complex cases with multiple comorbidities.